Revitalizing Science Education: Teachers' Response to Embedding Adat Bersendi Syara' and Syara' Bersendi Kitabullah Values into the Learning Process - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Neni Septiani; Miftahul Zannah Azzahra (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The primary objective of this research was to comprehensively examine the teachers' reactions and responses towards the implementation of Adat Bersendi Syara' and Syara' Bersendi Kitabullah values within the context of science subjects. Methodology: This study employs a descriptive quantitative research approach, targeting the entire teacher population of State Junior High School 1 Muaro Jambi, comprising 36 teachers. Using purposive sampling, 19 teachers were selected as the research sample. The research utilized a non-test instrument, namely a questionnaire, to gauge teacher responses. Data analysis was carried out through descriptive statistical tests. Main Findings: Based on the research, it is evident that teachers at State Junior High School 1 Muaro Jambi exhibited a highly favorable response, 52.6%. These findings indicate a positive reception among teachers regarding integrating Adat Bersendi Syara' and Syara' Bersendi Kitabullah values into the junior high school science curriculum. Novelty/Originality of this study: The novelty of this research is that by focusing on integrating culture and religious values, this research can accommodate the diversity of cultures and beliefs in the school environment. This can create an inclusive learning environment where every student feels valued and can identify themselves in the context of learning. Therefore, this research will complement previous studies.